Strategy to Fulfill The Need For Fisheries Supervisors To Support The Ministry Of Marine Affairs And Fisheries' Blue Economy Policy - Tomy Budi Mulianto; Asropi Asropi; Ridwan Rajab (Green Publisher Indonesia, 2024)
This study aims to analyze the factors that influence and formulate strategies to meet the needs of functional positions of fisheries supervisors and assistant fisheries supervisors in supporting the Blue Economy Policy of the Ministry of Maritime Affairs and Fisheries to be optimal. The research method used is a qualitative approach. The aspects of analysis include the state of work, the use of working time, and the goals that must be achieved based on the theory of workload indicators and Analytical Hierarchy Process (AHP) method. The results showed that the fulfillment of functional position needs was not optimal due to several factors, namely 1) the level of skills and understanding of some JF Waskan and Assistant Waskan was still quite low; 2) limited formation because there was no determination of latest position map; 3) Standard Operating Procedures (SOP) that differed between the center and UPT PSDKP; 4) fisheries supervision was still carried out manually with physical inspection of fishing vessels. For strategies to fulfill the needs of functional positions, several suggestions were formulated, namely 1) preparation of Human Capital Development Plan (HCDP) as a basis for training and development; 2) determination of the formation of the results of calculating the needs of functional positions in the latest position map; 3) improvement and refinement of SOPs; and 4) development of an independent fisheries monitoring system with risk assessment. Managerial implications are outlined in the priority strategy, while the highest factor is formation through accelerating the determination of the latest position map.